Adjustment/Equalizing Seizure As A Solution To The Filing Of Security Seizure On Objects Encumbered With Mortgage Rights - Zain, Muhammad Abyan; Rizkianti, Wardani (Universitas Muhammadiyah Sumatera Utara, 2025)
The creditor holding a mortgage has a prioritized position as stated in Law No. 4 of 1996 about Mortgage Rights on Land and Objects Related to Land. Issues may arise when the court grants a request for a security seizure on an object currently encumbered with a mortgage, as this could lead to overlapping rights over the same immovable property. Normative legal research is the method employed in this study, utilizing a statutory and case-based approach. The findings indicate that seizure cannot be applied to land rights encumbered with a mortgage; instead, only Adjustment/Equality Seizure can be imposed. Although a security seizure was initially requested on the mortgaged object, the court may automatically grant the request as an Adjustment/Equality Seizure. The creditor holding the mortgage retains a superior position compared to the holder of the Adjustment/Equality Seizure